The AI Google Voice Assistant on Ten Grade Students’ Speaking Skills at Vocational High School - Mahartana, I Komang Tri; Santosa, Made Hery; Dewi, Kadek SIntya (Universitas Pendidikan Ganesha, 2024)
There are challenges in students' speaking skills in Indonesia. These speaking problems are influenced by anxiety, difficulty in understanding, and language problems caused by lack of speaking practice. In the digital or modern era technology is possible to use as media for learning English. This study aims to analyze the effect of using Google Voice Assistant (GVA) on students' speaking skills. This study uses a mixed method of explanatory sequential with quantitative using quasi-experimental and qualitative by conducting interviews. The data sample was 10th grade students of vocational schools with experimental groups and control groups with 22 students in each group. Data were collected from pre-test and post-test. Based on statistical data analysis using SPSS, sig. (2-tailed is 0.096) was found which is higher than 0.005 meaning there is no significant effect. Interview data using the RASE model showed that students admitted that GVA was interesting as a speaking practice partner, but could not cover all aspects that could help students improve their speaking skills because of the familiarity principle which they were not familiar with, comprehensive assistance in providing materials, and lack of evaluative ability for their speaking skills. It can be said that GVA does not have a significant effect but can be developed as a pedagogical agent.